Association Between Daily Alcohol Intake and Risk of All-Cause Mortality - Liliani, Liliani; Fatmawati, Fatmawati (The International Journal of Medical Science and Health Research, 2024)
Background: The exploration of the association between daily alcohol intake and the risk of all-cause mortality has garnered significant attention in the academic literature, reflecting a complex interplay of health outcomes influenced by varying levels of alcohol consumption. Literature Review: The literature surrounding the association between daily alcohol intake and all-cause mortality presents a complex interplay of factors influencing health outcomes. The foundational research by (E Ronksley et al., 2011) emphasizes the ongoing debate over the cardioprotective effects of alcohol, revealing that while moderate consumption may correlate with lower cardiovascular mortality, the overall relationship with all-cause mortality remains intricate and influenced by the categorization of non-drinkers. Conclusion: In conclusion, the existing literature indicates that the relationship between daily alcohol intake and all-cause mortality is not straightforward. It is characterized by a J-shaped curve where moderate consumption may provide some protective effects, while excessive intake poses significant health risks. Methodological challenges, including the categorization of non-drinkers and the need for improved measurement of drinking patterns, underscore the complexity of this association. Public health guidelines must consider these nuances to effectively address the risks associated with alcohol consumption.